2022
DOI: 10.1029/2021jd035766
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Sand/Bed Collision Over the Gobi Surface

Abstract: The Gobi Desert is a vast semidesert area in China, which is mostly covered by gravel with minor vegetation. The Gobi in northern and northwestern part of China is believed to be the main source of sandstorms in East Asia (Sun et al., 2001), and the amount of dust released from the Gobi area (3.7 tons per day) during sandstorm is much higher than that from the sand desert area (0.8 tons per day; S. Chen et al., 2017). Dust emissions due to frequent sandstorms in the Gobi area (Jugder et al., 2012;Natsagdorj et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“…In this study, the main instruments used for the collision process included a natural particle emitter (Y. Chen et al., 2019; Zhang, Huang, & Dun, 2022); and an image acquisition system (PowerView HS‐2000 high‐speed camera), as shown in Figure 2c. Compared with acoustic sensor measurements, photoelectric measurements have better accuracy and stability (Shen et al., 2004) and have been successfully used in collision experimental studies (Y. Chen et al., 2019).…”
Section: Samples and Methodsmentioning
confidence: 99%
“…In this study, the main instruments used for the collision process included a natural particle emitter (Y. Chen et al., 2019; Zhang, Huang, & Dun, 2022); and an image acquisition system (PowerView HS‐2000 high‐speed camera), as shown in Figure 2c. Compared with acoustic sensor measurements, photoelectric measurements have better accuracy and stability (Shen et al., 2004) and have been successfully used in collision experimental studies (Y. Chen et al., 2019).…”
Section: Samples and Methodsmentioning
confidence: 99%
“…The coefficient of restitution, CoR = v r / v i , represents the proportion of the momentum of the saltating particle that is retained when it rebounds (Zhang et al, 2022). CoR decreased linearly with increasing N s (Fig.…”
Section: Coefficient Of Restitution and Splash Velocitymentioning
confidence: 99%
“…Because the collision occurs inside the near-surface boundary layer, the effect of air flow during a collision is negligible (Haff & Anderson, 1988, 1991. Many scholars have obtained splash functions by conducting particle-bed collision experiments without wind by using devices to launch the particles (Rioual et al, 2000(Rioual et al, , 2003Beladjine et al, 2007;Chen et al, 2019;Zhang et al, 2022). The most typical launch devices are launch guns and centrifugal launchers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gobi is a type of desert pavement widely distributed in Northwest China and Mongolia, and recent studies have shown that aeolian saltation over gobi differs from that over sand surfaces in the formation of a thicker saltation layer (e.g., Qu et al., 2023; Tan et al., 2020; Wang et al., 2022; Zhang et al., 2021) with nonmonotonic kinetic energy profiles (e.g., Tan et al., 2021) due to the difference in grain–bed collision processes (e.g., Tan et al., 2022; C. Zhang et al., 2022). These special characteristics make studies on aeolian sand transport over gobi very important in the field of aeolian research.…”
Section: Introductionmentioning
confidence: 99%